The Principle of Least Effort and Comprehension of Spoken Sentences by Younger and Older Adults - Ayasse, Nicolai D.; Hodson, Alana J.; Wingfield, Arthur (Frontiers in Psychology, 2021)
There is considerable evidence that listeners’ understanding of a spoken sentence need not always follow from a full analysis of the words and syntax of the utterance. Rather, listeners may instead conduct a superficial analysis, sampling some words and using presumed plausibility to arrive at an understanding of the sentence meaning. Because this latter strategy occurs more often for sentences with complex syntax that place a heavier processing burden on the listener than sentences with simpler syntax, shallow processing may represent a resource conserving strategy reflected in reduced processing effort. This factor may be even more important for older adults who as a group are known to have more limited working memory resources. In the present experiment 40 older adults (M age = 75.5 years) and 20 younger adults (M age = 20.7) were tested for comprehension of plausible and implausible sentences with a simpler subject-relative embedded clause structure or a more complex object-relative embedded clause structure. Dilation of the pupil of the eye was recorded as an index of processing effort. Results confirmed greater comprehension accuracy for plausible than implausible sentences, and for sentences with simpler than more complex syntax, with both effects amplified for the older adults. Analysis of peak pupil dilations for implausible sentences revealed a complex three-way interaction between age, syntactic complexity and plausibility. Results are discussed in terms of models of sentence comprehension, and pupillometry as an index of intentional task engagement.